A new karst dwelling species of the Gekko japonicus group (Squamata: Gekkonidae) from central Laos - Luu, Vinh Quang; Nguyen, Truong Quang; Le, Minh Duc; Bonkowski, Michael; Ziegler, Thomas (Zootaxa, 2017)
A new species of the Gekko japonicus group is described from Khammouane Province, central Laos, based on morphological characters and molecular data. Morphologically, Gekko nadenensis sp. nov. is differentiated from the remaining congeners by a combination of the following characters: size moderate (SVL 61.0–77.1 mm); nares bordered with rostral; internasals absent; postmentals enlarged; interorbital scales between anterior corners of the eyes 28–30; dorsal tubercles absent; ventral scales between mental and cloacal slit 175–185; midbody scale rows 123–140; ventral scale rows 38–40; subdigital lamellae on first toes 13–15, on fourth toes 14–16; finger and toe webbing present at base; tubercles on dorsal surface of fore and hind limbs absent; precloacal pores six (3+3 or 5+1) in a discontinuous row in males, absent in the female; postcloacal tubercles 1 or 2; tubercles absent on dorsal surface of tail base; subcaudals distinctly enlarged; dorsal surface of body with greyish brown blotches. Molecular analyses demonstrated the new species is closely related to G. bonkowskii and G. thakhekensis, but separated from them by approximately 7% in genetic divergence as shown by a fragment of the mitochondrial ND2 gene.